Defining operational objectives for nature-inclusive marine infrastructure to achieve system-scale impact - ter Hofstede, Remment; van Koningsveld, Mark (Frontiers in Marine Science, 2024)
The marine environment faces continuous anthropogenic pressures, including infrastructural developments at a global scale. Integration of nature-inclusive measures in the design of infrastructural development is increasingly encouraged, but a lack of coordination results in fragmentation of project-based measures, failing to meet the desired overall effects. To realize impact at system-scale, i.e. the seascape dimension required to achieve the set objective for a selected ecosystem component, overarching policies with shared targets towards effective nature-inclusive marine infrastructure are needed. We present a stepwise approach to work towards operational objectives for promoting selected ecosystem components that can be species, habitats or ecosystem processes, in which ruling policies, environmental conditions and the use of infrastructural development are aligned, and agreement on achievable ambitions is reached. Having clear targets will provide guidance to project developers in designing the infrastructure nature-inclusive, and in setting up relevant monitoring programs to evaluate the measures taken. We demonstrate how this stepwise approach could be applied to derive operational objectives for the design of nature-inclusive marine infrastructure in the context of offshore windfarm development in the North Sea, currently one of the most prominent infrastructure developments that changes the marine environment drastically. The European flat oyster Ostrea edulis has been selected as target species in the case study, as its once abundant population is now nearly extinct from the North Sea due to human disturbances, and there’s growing interest to restore its reefs. The application of the stepwise approach indicates the potential for oyster reef restoration in the area, based upon a clear match between ruling policy, environmental conditions, and habitat suitability within offshore wind farms. An agreement between the main stakeholders on achievable ambitions can likely be established and would translate into the operational objective to actively introduce oysters to reach an initial critical mass and optimize settlement habitat in all future offshore wind farms in an area with suitable habitat characteristics. Such an agreement on overarching objectives is crucial to align separate initiatives to promote targeted ecosystem components and to jointly become most effective, which is ultimately in the best interest of the larger community using the system.